“Zhores” — Petaflops supercomputer for data-driven modeling, machine learning and artificial intelligence installed in Skolkovo Institute of Science and Technology - Zacharov, Igor; Arslanov, Rinat; Gunin, Maksim; Stefonishin, Daniil; Bykov, Andrey; Pavlov, Sergey; Panarin, Oleg; Maliutin, Anton; Rykovanov, Sergey; Fedorov, Maxim (Open Engineering (Warsaw), 2019)
The Petaflops supercomputer “Zhores” recently launched in the “Center for Computational and Data-Intensive Science and Engineering” (CDISE) of Skolkovo Institute of Science and Technology (Skoltech) opens up new exciting opportunities for scientific discoveries in the institute especially in the areas of data-driven modeling, machine learning and artificial intelligence. This supercomputer utilizes the latest generation of Intel and NVidia processors to provide resources for the most compute intensive tasks of the Skoltech scientists working in digital pharma, predictive analytics, photonics, material science, image processing, plasma physics and many more. Currently it places 7 in the Russian and CIS TOP-50 (2019) supercomputer list. In this article we summarize the cluster properties and discuss the measured performance and usage modes of this new scientific instrument in Skoltech.